2014
DOI: 10.3109/10826084.2014.935948
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Combined-Use of Alcohol & Energy Drinks to Alcohol-Only on High-Risk Drinking and Driving Behaviors

Abstract: CU were more likely than AO to drive over the .08 BAC driving limit (53% vs. 38%; p = .009) and after knowing they were too drunk to drive (57% vs. 44%; p = .025). CU were also more likely (56% vs. 35%; p = .000) to ride with an intoxicated driver while knowing it was unsafe. Conclusions/Importance: Combined-users are more likely to drive after drinking, drive while knowingly drunk, and participate in other high-risk behaviors such as heavy drinking that increase the potential for injury. Public policy makers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 27 publications
4
48
1
Order By: Relevance
“…Our results in relation to smoking are partly in line with a newer systematic review, which found half significant and another half non-significant associations between loneliness and smoking [82]. In our study, lonely young (15 to 29 year old) and middle-aged (30 to 59 year old) participants, but not those of 60 years and older, smoked more often than participants who did not feel lonely.…”
Section: Discussionsupporting
confidence: 91%
“…Our results in relation to smoking are partly in line with a newer systematic review, which found half significant and another half non-significant associations between loneliness and smoking [82]. In our study, lonely young (15 to 29 year old) and middle-aged (30 to 59 year old) participants, but not those of 60 years and older, smoked more often than participants who did not feel lonely.…”
Section: Discussionsupporting
confidence: 91%
“…The failure to use condoms increases one's risk of HIV and other STDs. It is especially important to advance the understanding of inconsistent condom use in populations that are particularly at risk for HIV and other STDs, such as drug users (Mitchell & Latimer, 2009; Molitor et al, 1998; Nydegger, Ames, Stacy, & Grenard, 2014). Increasing our understanding of the perceived outcomes of condom use and related beliefs may help explain variation in this preventable behavior and contribute to the effectiveness of HIV prevention interventions.…”
Section: Introductionmentioning
confidence: 99%
“…As part of a larger study described previously (Foster, Neighbors, & Pai, 2015), undergraduate students were recruited from a psychology department via in-class recruitment and flyers placed around the university campus to participate in a study approved by the Institutional Review Board (IRB). Participants were 445 students ranging in age from 18–29 years (Mean age = 21.62, SD = 2.57, 82.7% female).…”
Section: Methodsmentioning
confidence: 99%